An islanding detection method for multi-DG systems based on high-frequency impedance estimation - Jia, Ke; Wei, Hongsheng; Bi, Tianshu; Thomas, David W.P.; Sumner, Mark (Institute of Electrical and Electronics Engineers, 2017)
Active islanding detection methods are generally employed for grid-connected inverter-based Distributed Generation (DG). However, there might be mutual influences and power quality issues caused by the disturbance signal when multiple inverters are involved. To address those problems, this paper analyzes the potential failure mechanism of the f-Q (frequency-reactive power) drifting active method in multiple-DG situations. Then, a novel high frequency transient injection based islanding detection method that is suitable for both single and multiple-DGs is proposed. Compared with the conventional injection methods, a high frequency impedance model for DG is provided for better theoretical analysis. By means of the intermittent Time Domain Low Voltage Condition (TDLVC) injection control, this method can achieve good accuracy and reduce disturbances to power system. 